2016
DOI: 10.1016/j.jss.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of peptidylarginine deiminase attenuates inflammation and improves survival in a rat model of hemorrhagic shock

Abstract: Background We have recently shown that inhibition of peptidylarginine deiminase (PAD) improves survival in a rodent model of lethal cecal ligation and puncture (CLP). The roles of PAD inhibitors in hemorrhagic shock (HS), however, are largely unknown. The goal of this study was to investigate the effects of YW3-56, a novel PAD inhibitor, on survival following severe HS. Methods Mouse macrophages were exposed to hypoxic conditions followed by reoxygenation in the presence or absence of YW3-56. Enzyme-linked i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
(32 reference statements)
2
6
0
Order By: Relevance
“…During HS, there is inadequate perfusion of the bowel which leads to epithelial damage; cellular injury during hypoperfusion and subsequent reperfusion can release proinflammatory cytokines in the circulation and trigger multiorgan failure 25. After HS, we observed that rats in the vehicle group had significantly increased levels of proinflammatory cytokines IL-1β and TNF-α, and CINC-1 in the intestine and serum, which is consistent with previous studies 26–28…”
Section: Discussionsupporting
confidence: 91%
“…During HS, there is inadequate perfusion of the bowel which leads to epithelial damage; cellular injury during hypoperfusion and subsequent reperfusion can release proinflammatory cytokines in the circulation and trigger multiorgan failure 25. After HS, we observed that rats in the vehicle group had significantly increased levels of proinflammatory cytokines IL-1β and TNF-α, and CINC-1 in the intestine and serum, which is consistent with previous studies 26–28…”
Section: Discussionsupporting
confidence: 91%
“…The survival outcome in the study by Biron et al (53) is similar to the other sepsis models (47) and the study by He et al (51). However, both He et al (51) and Pan et al (47) used a pan-PAD inhibitor instead of KO animals, which notably also inhibits PAD2. Given the conflicting findings, the pathophysiology of the two-hit hemorrhage and sepsis model and PADs remains to be further clarified.…”
Section: Trauma and Hemorrhagesupporting
confidence: 76%
“…In a previous study, PADI4 activation was associated with the exacerbation of kidney ischemiareperfusion injury by enhancing renal tubular inflammatory responses and neutrophil infiltration (27). In addition, PADI4 silencing in a rat model of hemorrhagic shock can attenuate local inflammatory responses (28). Other studies indicate that PADI4 can be involved in the prevention of bacterial infection by promoting the formation of neutrophil extracellular traps (29,30).…”
Section: Discussionmentioning
confidence: 95%